Effect of hypoalbuminemia on short-term outcomes after colorectal cancer surgery: A propensity score matching analysis - Kang, Bing; Zhao, Zhi-Qiang; Liu, Xiao-Yu; Cheng, Yu-Xi; Tao, Wei; Wei, Zheng-Qiang; Peng, Dong (Frontiers in Nutrition, 2022)
Purpose The purpose of our study was to investigate the effect of preoperative hypoalbuminemia on the short-term outcomes after primary colorectal cancer (CRC) surgery. Methods The retrospective study enrolled CRC patients who underwent primary surgery from Jan 2011 to Dec 2021 in a single teaching hospital. The short-term outcomes were compared between the hypoalbuminemia group and the normal group using propensity score matching (PSM). Univariate and multivariate logistic regression analyses were used for analyzing independent predictors of overall complications and major complications. Results A total of 7072 patients from a single center were enrolled in this study. There were 1078 (15.2%) patients in the preoperative hypoalbuminemia group and 5994 (84.8%) patients in the normal preoperative albumin group. After 1:1 PSM, there were 1028 patients in the hypoalbuminemia group and 1028 patients in the normal group. No significant differences were found in baseline information between the two groups after PSM. In terms of short-term outcomes, the hypoalbuminemia group had a longer operation time (p=0.003), greater volume of blood loss (p=0.036), longer hospital stay (p<0.01), higher proportion of overall complications (p=0.003), major complications (p=0.016), hinger incidence of pneumonia and abdominal infection (p=0.001) than the normal group after PSM. Furthermore, hypoalbuminemia was an independent predictor for overall complications (p=0.008) and major complications (p= 0.016). Conclusion Preoperative hypoalbuminemia increased overall complications and major complications after primary CRC surgery. Furthermore, hypoalbuminemia was an independent predictor for overall complications and major complications.